1990
DOI: 10.1038/bjc.1990.329
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the 31P magnetic resonance spectra of a rat tumour using vasodilators and its relationship to hypotension

Abstract: Summary The effects of different doses of hydralazine and prostacyclin on the 31P magnetic resonance spectra of the LBDS, fibrosarcoma were investigated and related to their effects on mean arterial blood pressure (MABP) and heart rate. The effect of reducing MABP by bleeding the animals, via the tail artery, was also investigated. Tumour spectral changes following high dose drug treatment (an (Hahn, 1974;Overgaard & Bichel, 1977;Overgaard & Nielsen, 1980). Hydralazine has also been shown to potentiate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 25 publications
(33 reference statements)
2
16
1
Order By: Relevance
“…However, this again is unlikely to be the explanation for the lack of effect with so many tumours in the 3"P-MRS studies; even in our experiments some 60% of the spontaneous tumours could be considered reasonably well oxygenated. Nor does it explain why hydralazine-induced changes in metabolic activity can be detected with 3'P-MRS in transplanted tumours (Okunieff et al, 1988;Bhujwalla et al, 1990;Tozer et al, 1990;Bremner et al, 1991). Clearly there is no easy explanation as to why our current study showed substantial effects of hydralazine in spontaneous tumours using measurements Of PO2 as the end point, and other studies using 3"P-MRS failed to find such effects.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…However, this again is unlikely to be the explanation for the lack of effect with so many tumours in the 3"P-MRS studies; even in our experiments some 60% of the spontaneous tumours could be considered reasonably well oxygenated. Nor does it explain why hydralazine-induced changes in metabolic activity can be detected with 3'P-MRS in transplanted tumours (Okunieff et al, 1988;Bhujwalla et al, 1990;Tozer et al, 1990;Bremner et al, 1991). Clearly there is no easy explanation as to why our current study showed substantial effects of hydralazine in spontaneous tumours using measurements Of PO2 as the end point, and other studies using 3"P-MRS failed to find such effects.…”
Section: Discussioncontrasting
confidence: 47%
“…This effect leads to changes in tumour oxygenation (Stratford et al, 1987;Horsman et al, 1989;Lin and Song, 1990;Fisker et al, 1991; Lemmon and Brown, 1991) and energy metabolism (Okunieff et al, 1988;Bhujwalla et al, 1990;Tozer et al, 1990;Bremner et al, 1991), and as a result this drug will enhance the anti-tumour activity of a range of agents. These include hypoxic cell cytotoxins such as bioreductive drugs Bremner et al, 1990) and hyperthermia (Horsman et al, 1989;Kalmus et al, 1990), as well as certain conventional chemotherapeutic agents such as melphalan (Stratford et al, 1987;Adams et al, 1989;Chaplin et al, 1989) and chlorambucil (Skarsgard et al, 1992).…”
mentioning
confidence: 99%
“…Any studies investigating changes in the energy status in tumours induced by physical, chemical or biological manoeuvres should thus be cognisant of alterations in blood flow. Changes in tumour blood flow following vasodilators Tozer et al, 1990), high-dose hyperthermia (Sijens et al, 1987;Kruger et al, 1991;Mayer et al, 1992), tumour necrosis factor a (TNF-a), lymphotoxin or interleukin 1 (Constantinidis et al, 1989;Kluge et al, 1992), X-irradiation (Tozer et al, 1989) or after i.p. mannitol administration are always followed by parallel alterations in tumour energy status.…”
mentioning
confidence: 99%
“…We established a technique appropriate for mice and estimated the mouse liver blood flow by in vivo 2 H NMR spectroscopy of D 2 O uptake after intravenous injection of D 2 O. Okunieff et al (1988) and Tozer et al (1990) reported that hepatic blood flow and energy metabolism are closely linked. In a recent study, Whalen & Shapiro (1991) measured liver blood flow using a D 2 O washout technique, using 2 H NMR and liver concentration of ATP and intracellular pH determined by 31 P NMR techniques in normal rats, and confirmed that liver blood flow rates are linked to liver ATP levels.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo 31 P NMR analysis of the liver was performed on Fe-deficient anaemic mice administered Cs extract. As blood flow and energy metabolism are thought to be linked (Okunieff et al 1988;Tozer et al 1990), 2 H NMR spectroscopy of deuterated water (D 2 O) uptake after intravenous injection of D 2 O was used to measure hepatic blood flow in the anaemic mice treated with Cs extract (Mattiello & Evelhoch, 1991;Zhao et al 1995). The in vivo structurebiological assessment techniques for energy metabolism and blood flow are useful not only for pharmaceutical and toxicological sciences but also for nutritional sciences.…”
Section: Nuclear Magnetic Resonance: Energy Metabolism: Chinese Medicinementioning
confidence: 99%